Life Skill Development and Transfer beyond Sport - Agnew Deborah; Jackson Kathryn; Pill Shane; Edwards Christine (Sciendo, 2019)
The aim of this research was to investigate the current life skills education programs offered by the Australian Football League (AFL) for elite footballers in order to determine the retention of life skill knowledge and transfer beyond sport. Life skill education in sport is an increasing phenomenon. Life skills sport programs are capable of delivering positive outcomes when nurtured through a deliberately designed curriculum and purposeful teaching strategies. However, it is not known how life skills are learned and importantly what the impact of life skills education on long term behavioural changes is. It is apparent from the literature that there is a need to identify how knowledge is acquired and importantly retained through life skills education programs. This was a qualitative research project from a life history perspective. Twenty footballers who had been delisted from an elite Australian football club and had subsequently returned to a South Australian state-based football club took part in semi-structured interviews. The data was analysed through an inductive thematic analysis. Two themes emerged from the data: football related development and holistic development. It was clear that football clubs placed importance on the development of life skills that transfer beyond the sport. However, given the footballers in this research have not fully transferred into life after sport, their perception of the broader transferability of their life-skill development beyond sport is limited. This research concludes that the current format of life skill education (delivering content) that the players in this study were exposed to was not effective because the players failed to be able to make connections from the program to life outside of football. Therefore, the programs are unlikely to have any long-term benefit to player health and well-being during their post-elite football life.